Impact of screen time on ADHD and Autism in children, and the role of parent-based interventions - Bukhari, Iqra; Bilal, Muhammad (Journal of the Pakistan Medical Association, 2026)
Autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD) are neurodevelopmental conditions that can significantly impair communication, social interaction, and learning abilities. The past decade has witnessed an unprecedented rise in screen time exposure among children, with emerging evidence suggesting concerning neurological implications that warrant clinical attention. We present the case of a five-year-old boy brought to our outpatient clinic with prominent hyperactivity, expressive speech delay, and poor eye contact. His developmental history revealed excessive screen use beginning at 12 months, often exceeding 5–6 hours daily with minimal parental interaction or structured activities. Initial assessment using standardised screening tools suggested features consistent with ASD and ADHD. However, following a structured intervention involving complete screen restriction for the first month, followed by gradual reintroduction with strict time limits (30 minutes daily), coupled with enhanced parent-child interactive play and structured daily routines, clinically significant improvement was observed. Within three months, his speech clarity improved significantly, social engagement increased, and hyperactive behaviours substantially decreased. This clinical vignette highlights the potentially underrecognised role of excessive screen exposure in mimicking or exacerbating neurodevelopmental symptoms. Current evidence increasingly supports these clinical observations. A comprehensive nationwide study of children from China demonstrated a clear dose-response relationship between screen time duration and behavioural and developmental problems, including ADHD and autism-related traits [1]. Similarly, a longitudinal study found that toddlers with higher screen exposure at 18 months exhibited significantly greater ADHD and autism symptoms, along with lower language and developmental scores by preschool age [2]. Most compellingly, a systematic review analysing data from over 53,000 children concluded that both the duration and early onset of screen exposure (particularly before 2 years) are associated with a significantly increased ASD risk, with some children demonstrating symptom improvement following screen use reduction [3]. The biological plausibility of these associations is supported by research indicating that excessive screen stimulation can alters dopamine and reward pathways, disrupts melatonin production affect sleep architecture, and may trigger attention-related behaviours that mimic ADHD symptomatology. Notably, controlled case studies have documented reversal of ADHD-like symptoms following systematic screen restriction interventions [4]. While pharmacological management remains a cornerstone in established ADHD care, evidence-based non-pharmacological interventions—including behavioural modifications, comprehensive parental training, and structured environmental approaches—are increasingly recognised as first-line components of treatment, particularly in younger children [5]. In this context, parental education and adherence to evidence-based screen time recommendations become crucial preventive measures.